Seeds of Decolonial Practice: An Autoethnographic Study of Settlers Working in Indigenous Communities - Fullerton, Meaghan E. (Canadian Journal of Counselling and Psychotherapy, 2021)
This autoethnographic study explores the process of cultivating a culturally safe and critically reflexive counselling practice in Indigenous contexts, an orientation that is imperative for settlers to work ethically with Indigenous clients, families, and communities. Any other approach risks recreating experiences of colonial violence in subtle or overt ways and eroding the therapeutic relationship. Research data generation included reflexive writing and interactive interviews with one female counselling therapists (aged 28) who, as a settler, has worked in multiple Indigenous communities. The analysis involved triangulation and using critical reflection and an understanding of cultural safety to interpret and learn from the data. Becoming unsettled is an emotionally evocative experience, but reflecting critically on discomforting emotions, reactions, and experiences is an essential component of personal transformation. Settlers cannot engage theoretically in decolonizing but rather must experience it first as individuals and then as ethically responsible citizens willing to challenge dominant cultural narratives and to help foster a more just society.